2017
DOI: 10.2147/ott.s123061
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival in renal cell carcinoma after introduction of targeted therapies: a Norwegian population-based study

Abstract: BackgroundThis population-wide retrospective, non-interventional registry study assessed changes in overall survival (OS) and factors influencing OS in Norwegian patients with renal cell carcinoma (RCC).MethodsTwo population-wide health registries were used to identify all RCC patients with (mRCC) or without metastases diagnosed before (2002–2005) and after (2006–2008 and 2009–2011) introduction of targeted therapies. Median OS was estimated using Kaplan–Meier method. Cox proportional hazards regression modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…The proportion of patients who received second-line treatment (50.6%) in the present study is consistent with most previously published observations, such as the study of Levy et al (52%) and Beisland et al (45% of the 2011 cohort) [ 28 , 29 ]. In the largest, IMDC registry-based study of 2106 patients with the median follow-up of 36 months, 43% received second line therapy [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…The proportion of patients who received second-line treatment (50.6%) in the present study is consistent with most previously published observations, such as the study of Levy et al (52%) and Beisland et al (45% of the 2011 cohort) [ 28 , 29 ]. In the largest, IMDC registry-based study of 2106 patients with the median follow-up of 36 months, 43% received second line therapy [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Novel drugs cabozantinib and immonotherapy drug nivolumab were shown to improve OS of mRCC patients after treatment failure with TKI-s [19,20]. According to more recent publication of phase Among national cohort studies of mRCC, there are 4 trials from Europe: Norwegian [15], Swedish [14] and Czech Republic [16] trial based on data from local registries and a Danish trial that used detailed and complete national data from medical records [13]. Our findings on the improvement of survival and treatment changes are comparable with those trials.…”
Section: Discussionmentioning
confidence: 99%
“…Danish Renal Cancer Group has evaluated the implementation of targeted therapy in a complete national cohort of patients, showing that this resulted in significantly improved treatment rates and overall survival [13]. Also, Swedish and Norwegian studies reported the contribution of targeted therapies to improved overall survival of mRCC patients [14,15]. Czech and Dutch studies have analyzed mRCC registry based data on targeted therapies use in their countries [16,17].…”
mentioning
confidence: 99%
“…National cancer treatment programmes and/or drug prescription registries that cover the whole country populations provided data on new anti-mRCC therapies within real-life patients [ 8 , 9 ]. Currently, patients who receive second-line therapy are expected to reach median overall survival (OS) over 27 months, while those who are enrolled in three or more lines of treatment may obtain over 43 months of OS and are greatest beneficiaries of RCC targeted therapies (TT).…”
Section: Introductionmentioning
confidence: 99%